Apoyo técnico y administrativo en proyectos de vivienda al fondo de vivienda obrera Duitama – Fomvidu (2023)
The project is based on an internship, supporting both technical and administrative tasks in the different processes carried out by the Workers' Housing Fund of Duitama (FOMVIDU). Among these processes currently developed by the Entity, there is the construction of new VIS and VIP housing from (2) two projects: Multifamiliar Guadalupe (16 apartments, 4 studio apartments, and 4 commercial spaces) and Ciudadela Residencial Abedules (200 apartments within the VIS and VIP category and 50 VIP houses); whose construction system is structural masonry, in which support is provided in the work supervision, preparation of construction logs, and progress reports. Likewise, it includes housing improvement programs, conducting technical visits to the different homes registered in the improvement programs. In this specific case, homes in the Vereda Tocogua; where, in addition to conducting technical visits, architectural surveys were also carried out, their digitalization, and the preparation of budgets according to the estimated work quantities.